Brief communication: Thwaites Glacier cavity evolution - Bevan, Suzanne L.; Luckman, Adrian J.; Benn, Douglas I.; Adusumilli, Susheel; Crawford, Anna (The Cryosphere, 2021)
Between 2014 and 2017, ocean melt eroded a large cavity beneath and along the western margin of the fast-flowing core of Thwaites Glacier. Here we show that from 2017 to the end of 2020 the cavity persisted but did not expand. This behaviour, of melt concentrated at the grounding line within confined sub-shelf cavities, fits with prior observations and modelling studies. We also show that acceleration and thinning of Thwaites Glacier grounded ice continued, with an increase in speed of 400 m a−1 and a thinning rate of at least 1.5 m a−1, between 2012 and 2020.